2016
DOI: 10.1186/s13058-016-0753-x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma exosome microRNAs are indicative of breast cancer

Abstract: BackgroundmicroRNAs are promising candidate breast cancer biomarkers due to their cancer-specific expression profiles. However, efforts to develop circulating breast cancer biomarkers are challenged by the heterogeneity of microRNAs in the blood. To overcome this challenge, we aimed to develop a molecular profile of microRNAs specifically secreted from breast cancer cells. Our first step towards this direction relates to capturing and analyzing the contents of exosomes, which are small secretory vesicles that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
394
6
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 475 publications
(436 citation statements)
references
References 44 publications
10
394
6
3
Order By: Relevance
“…HepG2) published by the Mendell laboratory (Chang et al 2015), as well as publicly available mature miRNA sequencing data from other laboratories (Bogerd et al 2014;Cao et al 2016;Hannafon et al 2016). By examining miRNAs with a higher mature-to-primiRNA ratio versus those with a lower ratio, we observed significant enrichment for optimal stem length or CNNC, and a stronger enrichment when both features were present (Supplemental Fig.…”
Section: Bulge Positions Control Hairpin Processingmentioning
confidence: 77%
“…HepG2) published by the Mendell laboratory (Chang et al 2015), as well as publicly available mature miRNA sequencing data from other laboratories (Bogerd et al 2014;Cao et al 2016;Hannafon et al 2016). By examining miRNAs with a higher mature-to-primiRNA ratio versus those with a lower ratio, we observed significant enrichment for optimal stem length or CNNC, and a stronger enrichment when both features were present (Supplemental Fig.…”
Section: Bulge Positions Control Hairpin Processingmentioning
confidence: 77%
“…2B). Since miR-1246 has significantly high expression at the extracellular level in MDA-MB-231 cells compared to HMLE cells and has been shown to play a vital role in breast cancer invasion and metastasis [13], we focused on miR-1246 in the following experiments. Furthermore, we analyzed the expression levels of miR-1246 in breast cancer and normal breast tissues by qRT–PCR.…”
Section: Resultsmentioning
confidence: 99%
“…showed that miR‐1246 was upregulated in exosomes from breast cancer cells compared to normal mammary epithelial cells and mouse plasma. When they analyzed human plasma samples, miR‐1246 and miR‐21 were detected at significantly higher levels in the plasma exosomes of 16 breast cancer patients as compared to the plasma exosomes of healthy control samples (Hannafon et al ., 2016). In another example, Zhang et al .…”
Section: Circulating Mirnas As Biomarkersmentioning
confidence: 99%